Sensitivity pattern of Salmonella species in different age groups - Farzeen Zehra; Syeda Mehak Fatima; Syedain, Fatima (International Journal of Endorsing Health Science Research, 2015)
Objective: To determine the current efficacy of antibiotics used in treatment of enteric fever, with respect to age, in a laboratory setting. Study Design: A cross-sectional study. Methodology: A retrospective study was done on 105 specimens that were collected at Dr. Essa Laboratory and Diagnostic Centre from January 2012-December 2013. These specimens were inoculated into blood cultures bottles having Oxoid and incubated. Positive specimens were then cultured on EMB, CLED and chocolate agar. These sub cultures were incubated at 37°C for about two days.With AP120E screening was done of suspected colonies. They were then processed. Identified isolates were confirmed by specific agglutination antisera. Kirby–Bauer disc diffusion method was used to confirm anti-microbial suspects by Mueller-Hinton agar (Oxoid), using eleven antibiotics which were Amoxicillin , Ciprofloxacin , Aztreonam , Cefixime , Cefotaxime , Ceftriaxone , Co-trimaxole, Enoxacin , Fosfomycin, Sparfloxacin , and Ofloxacin. Results: The overall sensitivity profile shown by these antibiotics against Salmonellae species is as follow : Amoxicillin (0 ) , Aztreonam (47.6%) , Cefixime (98.1%) , Cefotaxime (98.1%) , Ceftriaxone (97.1%) , Ciprofloxacin (85.7%) , Co-trimoxazole (64.8%) , Enoxacin (28.6%) , Fosfomycin (85.7%) , Ofloxacin (94.3%) , Sparfloxacin (30.5%). Conclusion: Third generation cephalosporins (Cefixime, Cefotaxime, Ceftriaxone) have maximum sensitivity profile among all age groups, rendering them most suitable for empirical treatment.